After the global crisis - Domenico Mario Nuti (Transformation, Integration and Globalization Economic Research (TIGER), 2011)
Conjectures about the post-crisis future of the global economy are path-dependent, i.e. they necessarily depend on the course of events envisaged for getting out of the crisis. By and large, the economic system emerging from the crisis is bound to be substantially very similar to the pre-crisis one, improved in some respects, but worsened by large scale cuts in welfare expenditure made necessary by the (debatable) purpose of achieving fiscal balance. The post-crisis system will be more conflictual and insecure, more unequal and less cohesive, less rather than more "green" - basically a more unpleasant world in which to live. It need not be so.
Keywords: 330